Respuesta :

Sorry for the delay but I answered your question and the answer is -6xsquare +11x-4

Ver imagen jeswin

Answer:

The standard form is [tex]-6x^2+11x-4[/tex]

Step-by-step explanation:

Given : [tex](-3x+4)(2x-1)[/tex]

We have to multiply [tex](-3x+4)(2x-1)[/tex]

Consider the given [tex](-3x+4)(2x-1)[/tex]

[tex]\mathrm{Apply\:FOIL\:method}:\quad \left(a+b\right)\left(c+d\right)=ac+ad+bc+bd[/tex]

Here, a = 3x , b = 4 , c = 2x , d = -1

[tex]=\left(-3x\right)\cdot \:2x+\left(-3x\right)\left(-1\right)+4\cdot \:2x+4\left(-1\right)[/tex]

Apply plus- minus rule, [tex]+\left(-a\right)=-a,\:\:\left(-a\right)\left(-b\right)=ab[/tex]

[tex]=-3\cdot \:2xx+3\cdot \:1\cdot \:x+4\cdot \:2x-4\cdot \:1[/tex]

Simplify, by adding similar terms, we get,

[tex]=-6x^2+11x-4[/tex]

Thus, The standard form is [tex]-6x^2+11x-4[/tex]